A general surface-treatment-free approach to fabrication of alignment layers using a super-aligned carbon nanotube film template - 付伟琦 魏洋 朱峰 刘亮 姜开利 李群庆 范守善 (Chinese physics B, 2010)
We develop a general approach to the fabrication of films with unidirectional grooves, such as silicon nitride, silicon dioxide and aluminium oxide, in which the surface is not required to be treated. Super-aligned carbon nanotube （SACNT） film may be used as a template and as sacrificial layer, which is subsequently removed by heating in an atmosphere of air. The unidirectional morphology of the SACNT film turns into a desired film, which is found to possess the ability to align liquid crystal molecules. This approach also features high efficiency, low cost and easy scaling-up for mass production.